1997
DOI: 10.1038/sj.bjp.0700947
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide formation in the ductus arteriosus in the lamb: implications for the regulation of muscle tone

Abstract: 1 We have previously shown that carbon monoxide (CO) potently relaxes the lamb ductus arteriosus and have ascribed this response to inhibition of a cytochrome P450-based mono-oxygenase reaction controlling the formation of endothelin-1 (ET-1). In the present study, we have examined whether CO is formed naturally in the vessel. 2 The CO-forming enzyme, haem oxygenase (HO), was identi®ed in ductal tissue in its constitutive (HO-2) and inducible (HO-1) isoforms by Western immunoblotting and immunological staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 38 publications
2
58
1
Order By: Relevance
“…If so, it might be expected that carbon monoxide could block basal nitric oxide production and cause vasoconstriction with a consequent increase in blood pressure. While these two functionally opposing roles of endogenously formed carbon monoxide in vascular tone are equally plausible, several studies using isolated vessels and perfused preparations (7,(53)(54)(55)(56) have suggested that hemederived carbon monoxide may be vasodilatory. Such reports have understandably typified carbon monoxide as a vasodilator.…”
Section: Endogenous Carbon Monoxide and Vascular Tone: Dual Actions Cmentioning
confidence: 99%
“…If so, it might be expected that carbon monoxide could block basal nitric oxide production and cause vasoconstriction with a consequent increase in blood pressure. While these two functionally opposing roles of endogenously formed carbon monoxide in vascular tone are equally plausible, several studies using isolated vessels and perfused preparations (7,(53)(54)(55)(56) have suggested that hemederived carbon monoxide may be vasodilatory. Such reports have understandably typified carbon monoxide as a vasodilator.…”
Section: Endogenous Carbon Monoxide and Vascular Tone: Dual Actions Cmentioning
confidence: 99%
“…Concentrations of the inhibitors were derived from the literature with the aim of combining efficacy with selectivity. In particular, at the stated concentrations, ZnPP exerts a specific effect on the HO enzyme complex in the ductus (21).…”
Section: Animalsmentioning
confidence: 99%
“…Furchgott and Jothianandan (1991) reported that CO, arising from the metabolism of heme by HO, dilated blood vessels, whereas inhibition of HO by tinmesoporphyrin (SnMP) produced vasoconstriction (Kozma et al, 1999) and raised blood pressure (Johnson et al, 1995(Johnson et al, , 1996. Heme, by activating HO, has been shown to dilate the ductus arteriosus (Coceani et al, 1997). Moreover, contiguous, if not overlapping, spheres of activity within the vasculature of nitric oxide (NO) and CO were suggested by the study of Zakhary et al (1996).…”
mentioning
confidence: 99%